1996
DOI: 10.1007/s002130050131
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic localisation of D 3 -dopamine receptors in the human brain using the selective D 3 -dopamine receptor agonist (+)-[ 3 H]PD 128907

Abstract: The selective D3-dopamine receptor agonist 4aR, 10bR-(+)-trans-3,4,4a, 10b-tetrahydro-4-[N-propyl-2,3-3H]-2H,5H-[1] benzopyrano[4,3-b]-1,4-oxazin-9-ol ([3H]PD 128907) was used to visualise D3-dopamine receptors in whole hemisphere cryosections from post-mortem human brain. [3H]PD 128907 has an 18- to 40-fold selectivity for D3- over D2-dopamine receptors as compared to a 7- to 24-fold selectivity of the more commonly used ligand [3H]7-OH-DPAT. [3H]PD 128907 accumulated markedly in the nucleus accumbens and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 31 publications
1
68
0
Order By: Relevance
“…Linkage in the presence of association was positively demonstrated by the use of the Transmission Disequilibrium Test (TDT) in families with both parents available and at least one heterozygous parent (families 2,9,12,14,19,21) or the Sib-TDT (S-TDT) in other informative sibships (families 7,8,15,17,18,25,26,28,30) (18). TDT 2 value was 7.364 (P ϭ 0.0067), and S-TDT zЈ score was 4.306 (P Ͻ 0.00001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linkage in the presence of association was positively demonstrated by the use of the Transmission Disequilibrium Test (TDT) in families with both parents available and at least one heterozygous parent (families 2,9,12,14,19,21) or the Sib-TDT (S-TDT) in other informative sibships (families 7,8,15,17,18,25,26,28,30) (18). TDT 2 value was 7.364 (P ϭ 0.0067), and S-TDT zЈ score was 4.306 (P Ͻ 0.00001).…”
Section: Resultsmentioning
confidence: 99%
“…DRD3 expression is reduced in Parkinson's disease (PD) (13), and a study in a monkey model of PD indicates that DRD3 hyperfunction is responsible for dyskinesia, a motor complication of PD treatment (14). Largest DRD3 densities occur in the basal ganglia, but cerebellum also expresses DRD3 at a lower density (15). In the rat cerebellum, DRD3 is present in Purkinje cells (16), and cerebellum has been implicated in the pathogenesis of ET (17).…”
mentioning
confidence: 99%
“…First, in vitro competition studies have shown that D 2 -like receptors expressed in human membranes of the GP have high affinity for DA and are all guanine-nucleotide-insensitive (De Keyser et al, 1989). This finding suggests that these receptors actually correspond to D 3 -rather than to D 2 high receptors, as those two properties are characteristic of the D 3 receptor (Sokoloff et al, 1990 (Gurevich and Joyce, 1999;Hall et al, 1996;Murray et al, 1994). It thus appears that while the anatomic distributions of D 3 and D 2 receptors largely overlap in the basal ganglia, their quantitative ratios (i.e., D 3 /D 2 ratios) differ between structures, being highest in nucleus accumbens, ventral putamen, Islands of Calleja and GP, and lowest in dorsal striatum (Gurevich and Joyce, 1999;Murray et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Low to moderate densities are present in the caudate-putamen, anterior and medial thalamic nuclei, amygdala, hippocampal CA region, cortical regions (particularly the anterior cingulate and subcallosal gyrus), lateral geniculate body, substantia nigra pars compacta, locus ceruleus, and median raphé. Receptor binding data also indicate the presence of D 3 receptors in the NAc, internal globus pallidus, ventral pallidum, septum, islands of Calleja, amygdala, and VTA [120,124,132,162,205]. Interestingly, significant inter-species differences have been reported in the distribution of D 3 receptors [176].…”
Section: Human Da D 3 Receptor Localization Under Basal Conditionmentioning
confidence: 91%